Analisis Jenis Pelatihan Pernapasan : Teknik Pernapasan dan Olah Vokal : Pelatihan Voice Over - Kustiawan, Winda; Marshanda, Siti Annisa; Nabila, Vira; Suciono, M. Wahyu; Alya, Heny Trie Dina; Djuniardi, Rakhas (YASIN, 2023)
In doing voice over, several exercises are carried out to support voice over abilities, namely breathing training and vocal training. Each of these trainings has a different type and is important for both breathing and speaking skills. For this reason, this study wanted to find out the analysis of the types of breathing training in the form of breathing techniques as well as vocal training in voice over. The method used in this research is descriptive qualitative with data library research analysis techniques which are at the stages of data reduction, data presentation, and drawing conclusions. Based on the research findings, it was found that the types of breathing techniques or training included several things, namely diaphragmatic breathing exercises, pursed lips breathing, lions breath, equal breathing and deep breathing. Meanwhile, vocal training for voice over includes intonation techniques, breathing techniques, carrying techniques, and articulation techniques. Various types and techniques in breathing and vocal exercises can be carried out as routine exercises to get the right functions and benefits for voice over talent in carrying out their duties and profession.